2004
DOI: 10.1200/jco.2004.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Molecular Upstaging of Paraffin-Embedded Sentinel Lymph Nodes in Melanoma Patients

Abstract: Purpose-Detection of micrometastases in sentinel lymph nodes (SLNs) is important for accurate staging and prognosis in melanoma patients. However, a significant number of patients with histopathology-negative SLNs subsequently develop recurrent disease. We hypothesized that a quantitative realtime reverse transcriptase polymerase chain reaction (qRT) assay using multiple specific mRNA markers could detect occult metastasis in paraffin-embedded (PE) SLNs to upstage and predict disease outcome.Patients and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
135
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 30 publications
2
135
0
1
Order By: Relevance
“…Sentinel lymph node tissue that is negative by histology and immunohistology may have RT-PCR evidence of possible occult metastases. [39][40][41][42] However, because of the inevitable cell destruction during RNA extraction, solution-phase RT-PCR cannot identify the cellular source of any amplified signals for mRNA. In this study, we have shown that it is possible to detect MART-1 mRNA and TRP-2 mRNA in archival FFPE tissue sections of melanoma by a one-step RT in situ PCR technique.…”
Section: Discussionmentioning
confidence: 99%
“…Sentinel lymph node tissue that is negative by histology and immunohistology may have RT-PCR evidence of possible occult metastases. [39][40][41][42] However, because of the inevitable cell destruction during RNA extraction, solution-phase RT-PCR cannot identify the cellular source of any amplified signals for mRNA. In this study, we have shown that it is possible to detect MART-1 mRNA and TRP-2 mRNA in archival FFPE tissue sections of melanoma by a one-step RT in situ PCR technique.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with positive SLNs by conventional and qRT assessment experience the worst outcomes, whereas those with negative SLNs using these combined techniques have the best prognosis. Interestingly, the risk associated with qRT-positive SLNs is not uniform; it seems to vary directly with the number of molecular markers detected [Takeuchi et al, 2004].…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Investigators have improved the sensitivity and specificity of the RT-PCR assay by employing multi-marker panels in peripheral blood analysis [Hoon et al, 1995;Curry et al, 1998;Bostick et al, 1999;Hoon et al, 2000;Boi et al, 2002;Kuo et al, 2003;Takeuchi et al, 2004]. Hoon et al [1995] used a multi-marker panel of tyrosinase and tumor-associated antigens melanotransferrin (p97), melanoma antigen gene A3 (MAGE-3) and an adhesion-related glycoprotein, melanoma cell adhesion molecule (MUC18) to assay the blood of 119 stage I-IV melanoma patients by RT-PCR.…”
Section: Multi-marker Rt-pcrmentioning
confidence: 99%
See 2 more Smart Citations